The Chinese Version of the Barratt Impulsiveness Scale-11: Reassessment of Its Psychometric Properties in Three Adolescent Samples. Issue 3 (2016) - Wan, Yan, Manru Zhang; Jin, Fengxian; Cheng, Zaohuo
No abstract available